2013
DOI: 10.1073/pnas.1303006110
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric regulation of SERCA by phosphorylation-mediated conformational shift of phospholamban

Abstract: The membrane protein complex between the sarcoplasmic reticulum Ca 2+ -ATPase (SERCA) and phospholamban (PLN) controls Ca 2+ transport in cardiomyocytes, thereby modulating cardiac contractility. β-Adrenergic-stimulated phosphorylation of PLN at Ser-16 enhances SERCA activity via an unknown mechanism. Using solid-state nuclear magnetic resonance spectroscopy, we mapped the physical interactions between SERCA and both unphosphorylated and phosphorylated PLN in membrane bilayers. We found that the allosteric reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
196
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(214 citation statements)
references
References 46 publications
15
196
1
1
Order By: Relevance
“…It has been reported that PLN inhibits Serca2a activity by decreasing the apparent affinity of the Serca2a for Ca 2+ , and this inhibition is relieved by phosphorylation of PLN at serine 16 or threonine 17 41. This suggests that the activity of Serca2a in TAC‐induced cardiac hypertrophy is inhibited because of decreased phosphorylation of PLN, resulting in a decrease in the rate of relaxation of cardiac muscle and a positive inotropic effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PLN inhibits Serca2a activity by decreasing the apparent affinity of the Serca2a for Ca 2+ , and this inhibition is relieved by phosphorylation of PLN at serine 16 or threonine 17 41. This suggests that the activity of Serca2a in TAC‐induced cardiac hypertrophy is inhibited because of decreased phosphorylation of PLN, resulting in a decrease in the rate of relaxation of cardiac muscle and a positive inotropic effect.…”
Section: Discussionmentioning
confidence: 99%
“…SERCA2a activity is allosterically inhibited by Pln. Phosphorylation of Pln at Ser16/Thr17 sites -by PKA and CaMK, respectively -relieves this inhibition and enhances SERCA2a activity (31,32). Hence, we next measured the phosphorylation status of Pln in Tead1-deleted hearts.…”
Section: Tead1 Regulates Serca2a Activity In a Cell-autonomous Mannermentioning
confidence: 99%
“…The R9C-dependent structural transition and the phosphorylation-dependent conformational change are similar in direction and magnitude (ϩ1.2 and ϩ4 Å, respectively). A regulatory complex structural change is the primary mechanism for relief of inhibition of SERCA by PLB phosphorylation (50,51). How the R9C mutation may imitate phosphorylation of PLB is not clear, but we speculate that there may be modification of the Cys at position 9 to a negatively charged species that resembles phosphorylated residues of neighboring PKA/CaMKII sites on the PLB.…”
Section: Discussionmentioning
confidence: 99%